Scurvy in a Child with with Recurrent Lower Extremity Weakness: A Case Report - Akhmad Rizki Farhan; Shinta Nareswari (Medula, 2026)
Scurvy is a disease caused by vitamin C deficiency that is still encountered in children with restrictive eating patterns and severe malnutrition. Musculoskeletal manifestations, including lower limb pain, refusal to walk, pseudoparalysis, and joint swelling, often mimic neurological, infectious, or rheumatologic disorders, leading to delayed diagnosis. A 3-year-7-month-old boy presented with recurrent inability to walk accompanied by pain and swelling in both knees. Five months earlier, he had experienced fever followed by bilateral lower limb weakness and inability to stand. At that time, he was diagnosed with scurvy at another hospital and showed improvement after receiving vitamin C supplementation and physiotherapy. Twelve days before admission, similar symptoms recurred, accompanied by oral ulcers. Physical examination revealed severe malnutrition, stunting, microcephaly, tenderness of both knees, and lower extremity weakness. Laboratory evaluation demonstrated leukopenia (3,700/μL). Bilateral genu radiographs showed metaphyseal osteopenia of the femur, a soft tissue lucency at the distal femur suggestive of hematoma, and bilateral Wimberger sign, which is characteristic of scurvy. Dietary history revealed refusal to consume fruits, vegetables, milk, and protein-rich foods, with a preference for packaged snack foods. The patient was treated with intravenous vitamin C at a dose of 300 mg/day for 7 days, followed by oral vitamin C 100 mg/day for 1 month, in addition to nutritional rehabilitation, multivitamin supplementation, and physiotherapy. Rapid clinical improvement following treatment highlights the importance of obtaining a thorough dietary history and recognizing characteristic radiographic findings to establish an early diagnosis and prevent complications.